Winnipeg: The Northern Anchor of the Wholesale Trade - Eaton, Leonard (Urban History Review / Revue d'histoire urbaine, 1982)
After 1882, the city of Winnipeg rose to control the wholesaling trade of western Canada. In the process of achieving dominance over the vast territory stretching from the Great Lakes to the Rocky Mountains, the jobbers of the city created a warehouse district of unusual architectural distinction. Men like George D. Wood, C.H. Whitla and J.H. Ashdown should be recognized as major patrons of architecture. Their chief designer, J.H. Cadham, should also be identified as a figure of commanding interest. This article seeks to put this important development in architectural and urban history in its appropriate setting.